PENGARUH MODAL, LUAS LAHAN DAN TEKNOLOGI TERHADAP PENDAPATAN PETANI PADI DI SUBAK SEMPIDI, KECAMATAN MENGWI, KABUPATEN BADUNG - I GUSTI AYU LIA YASMITA (Universitas Mahasaraswati K. Mataram, 2023)
This study is to find out how big is the effect of capital, land area and technology on farmers’ income level in Mengwi sub-district, Badung regency. This study was descriptive quantitative research, the data processed by the needs of the model used. The source of the data were interview, documentation and data collection sheet. The total of population in this study was 223 people, and the total of sample was 70 respondents. The data was processed by classical assumption test and hypothesis test and heteroscedasticity, normality test, multicollinearity test, autocorrelation test and the data analyzed by multiple linear regression method. The result of the study showed that simultaneously the variable of capital, land area, and technology influenced significant and positive on farmers’ income. Partially capital, land area and technology influenced significant and positive on farmers’ income in Mengwi sub-district Badung regency. The estimation was done to measure proportion and percentage from variation total of dependent variable which able to explained by regression model. From the result of regression above R square (R2) was 0,786 which means the independent variable explained the variation of farmers’ income in Subak Sempidi Mengwi sub-district, Badung regency of 78,6% affected by capital, land area and technology. While the rest 21,4% explained by others variables outside of the study.